Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter P - P.1 - Graphs and Models - Exercises: 65

Answer

(-3,$\sqrt 3$)(-2,2)

Work Step by Step

$ \sqrt {x+6}$ = $\sqrt {-x^{2}-4x }$ Equate the two equations in terms of x since we have the same y in each case $ {x+6}$ = $ {-x^{2}-4x }$ squaring on both sides $x^{2} +x +4x+6=0$ moving x terms to one side of the equation $x^{2} +5x+6=0$ Solving the equation $(x+2)(x+3)=0$ Solving the equation $x=-2,x=-3$ we get two values for x $y=\sqrt {-2+6} =2$ solving for y with x=-2 $y=\sqrt {-3+6} =\sqrt 3$ solving for y with x=-3 And the answer is (-3,$\sqrt 3$)(-2,2)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.